Anthracnose of Stylosanthes capitata: Implications for future disease evaluations of indigenous tropical pasture legumes - Lenné, Jillian M.; Thomas, D.; Andrade, Ronaldo P. de; Vargas, A. (Scientific Societies, 1984)
During field screening from 1978 to 1981 of 121 accessions of the tropical pasture legume Stylosanthes capitata at two sites in Colombia and at Planaltina in Brazil, 94.2% of the accessions were resistant to anthracnose (caused by Colletotrichum gloeosporioides) in Colombia while 85.1% were susceptible in Brazil. In comparative seedling pathogenicity studies with isolates from both countries, isolates pathogenic to a wide range of accessions of S. capitata were only found in Brazil. Results strongly suggest that specialized isolates of C. gloeosporioides pathogenic to S. capitata exist in Brazil (the native habitat and probable center of diversity of this legume) and not in Colombia where S. capitata is an exotic species. This implies the need to screen indigenous tropical pasture legumes for disease resistance in their native habitats and the need for international collaborative disease screening trials in the future.